The Effect of Health Counseling Through Snakes and Ladders Games on Increasing Adolescent Knowledge About Malaria - Romauli, Suryati; Whardani, Yeni (Universitas Islam Jember, 2024)
Malaria is an infectious disease caused by the plasmodium parasite that lives and multiplies in human red blood cells transmitted by female Anopheles mosquitoes. Malaria attacks all age groups, one of which is adolescence, therefore a proper information is required from health workers, by providing counseling through snakes and ladders games. This study aims to determine the effect of health counseling through snakes and ladders on increasing adolescent knowledge about malaria. Method: This type of research is quasi-experimental with a pretest posttest design with control group. The population is all class IX teenagers numbering 80 students. A sample of 44 students was taken using a simple random sampling technique, divided into 22 samples for the intervention group and 22 samples for the control group. The instrument used was a questionnaire consisting of adolescent characteristics and 15 knowledge questions about malaria. Counseling aids in the form of snakes and ladders games about malaria. Results : Before being given the snakes and ladders game in the intervention group most 90.9% had less knowledge about malaria, while in the control group most 86.4% also had less knowledge. After being given the snakes and ladders game in the intervention group most 59.1% had good knowledge about malaria and a small part of 40.9% had sufficient knowledge, while in the control group most 68.2% had less knowledge and a small part 31.8% had enough knowledge. The results of the Independet test sample T-test obtained ρ value of 0.000 < 0.05.